The Role of ICT in Human Resources in the Education Sector: Peran TIK dalam Sumber Daya Manusia di Bidang Pendidikan - Bahar, Herwina; Daryo, Daryo (ITScience (Information Technology and Science), 2024)
Advances in computer information technology have a significant impact on the world of education. Because each person has the ability to do it themselves, the world of education has the ability to explore high-quality learning materials, such as literature, journals, and books, as well as build scientific discussion forums and consult with experts around the world. This journal was created to find out how big the influence of Information Technology and Computers is on education. This research is a type of literature study which aims to explain research findings collected from articles and books related to the subject being discussed. According to research results in this journal, innovative and creative learning models can be accessed through technological advances. According to research results published in this journal, innovative and creative learning models can be accessed through technological advances. The development of human resources in the education sector depends on advances in technology and information. It is hoped that educators can adapt to advances in information and communication technology (ICT). The author comes to the conclusion that educators must be able to adapt to increasingly complex and sophisticated developments in the modern era 4.0. However, the role of human resources must be consistent with advances in technology and information. Therefore, trained teaching staff are needed to help improve students' abilities. Example, mentor and role model for his students.